Noise Monitoring Networks as Tools for Smart City Decision-Making - SÁNCHEZ-SÁNCHEZ, Rafael; FORTES-GARRIDO, Juan Carlos; BOLÍVAR, Juan Pedro (Archives of Acoustics, 2018)
Noise Monitoring Networks (NMNs) have been implemented in many cities by town councils, allowing them to know, in real time, the environmental noise levels in the busiest streets by the continuous measurement of selected acoustic parameters throughout the year. NMNs are aimed at: 1) detecting areas of the city that breach guidelines for acoustic quality objectives; 2) obtaining noise data needed to develop and implement action plans; and 3) informing the public about the permissible acoustic pollution for different districts and times of day. The aim of this work was to analyse data from the NMN of the city of Huelva (Spain), in order to study the influence on the noise of re-asphalting the busiest streets. The street pavements improve LAeq, 24 h from 3 up to 8 dB(A), depending on the type of the route. These results could be used by council authorities in deciding when to undertake the re-asphalting of the streets of Huelva, and to select the type of asphalt that should be used.